Dreadful young ladies and other stories - Barnhill, Kelly Regan (Algonquin Books of Chapel Hill, 2018)
A short story collection featuring elements of magic realism while touching on the themes of love, knowledge, grief, hope, and jealousy. Teeming with uncanny characters whose lives unfold in worlds at once strikingly human and eerily original, these stories demonstrate the strength and power -- known and unknown -- of the imagination.